MEDIA EDUKATIF TENTANG HEWAN AIR TAWAR BERBASIS AUGMENTED REALITY DENGAN TEHNIK SUPERIMPOSITION - Irawan, Feby; Ramdhan, Syaipul; Sudaryana, I Ketut (ISTEK WIDURI, 2023)
Augmented Reality (AR) is revolutionizing human-computer interaction by blending the physical and virtual worlds. AR learning using markers or markerless has been widely used in learning media. However, both have a level of saturation because it has been repeated. The learning process of Kindergarten students requires learning that is interesting and fun, so this study explores learning freshwater fish using AR for children and emphasizes the importance of interactivity-centered design through 3-dimensional real objects. The approach is carried out using a superimposition technique that allows real 3-dimensional objects to become varied markers. The test results at the scan angle of the papercraft object used at a distance of 50cm with a slope of 1800, 50cm with a slope of 1300, 50cm with a slope of 900. Likewise the test results on respondents between ordinary learning using the AR application found 83.4% for ordinary learning and 100 % to study with the app. In the end, this research tries to present a new method in markers with a more interesting and real Superimposition technique.